2012
DOI: 10.1177/1470593112451395
|View full text |Cite
|
Sign up to set email alerts
|

From commodity fetishism to commodity narcissism

Abstract: Marketing and consumer researchers have taken an increasing interest in the prevalence of and possibilities for enlightened consumerism. Contemporary studies show us, though, that ethically concerned consumers rarely act on their concerns – instead they act as if they were unenlightened about the negative effects of their consumption. The paper advances a theory for this contradiction that draws on Marx’s work on commodity fetishism and Freud’s analysis of sexual fetishism. In an attempt to reconcile the struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
100
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 38 publications
3
100
0
Order By: Relevance
“…Freud (1975) alerts us to the narcissistic strand running through consumption whereby purchases are made to satisfy desires and add to idealised images of selves (Cluley & Dunne, 2012). Consumer culture in general may be linked to the mobilisation of a narcissistic self-identity (Wearing, McDonald, & Wearing, 2013) as selves are increasingly fashioned and differentiated through aesthetic consumption practices (Shields, 2003).…”
Section: Narcissism Environmental Factorsmentioning
confidence: 99%
“…Freud (1975) alerts us to the narcissistic strand running through consumption whereby purchases are made to satisfy desires and add to idealised images of selves (Cluley & Dunne, 2012). Consumer culture in general may be linked to the mobilisation of a narcissistic self-identity (Wearing, McDonald, & Wearing, 2013) as selves are increasingly fashioned and differentiated through aesthetic consumption practices (Shields, 2003).…”
Section: Narcissism Environmental Factorsmentioning
confidence: 99%
“…Salzer-Mörling and Strannegård 2007;Cluley and Dunne 2012). Furthermore, the paper indicates that reflexive critique and cynicism do not always constitute an effective form of resistance (cf.…”
Section: J Bertilssonmentioning
confidence: 89%
“…From their perspective, morality is merely used by a majority of members to put up what Sloterdijk (1987) refers to as a façade of civility, grace and political correctness. It is argued that the morals conveyed are contrived, false and untrue in relation to what young people are really doing and that the previous moral conceptions merely represent an idealist image that is disconnected from the consumers' real behavior (see Chatzidakis, Hibbert, and Smith 2007;Salzer-Mörling and Strannegård 2007;Cluley and Dunne 2012;Markkula and Moisander 2012). Connections are again here made to a left-wing and socio-democratic Scandinavian ethos, which does not allow for income discrepancies and does not allow people to stand out from, or to be financially better off than, the great middle.…”
Section: Rainbowmentioning
confidence: 99%
“…In sum, analysing how culture and religion can affect a child's toilet training—and, by extension, their later psychological development—could enhance our comprehension of the relationship between defecation‐related problems and consumers' personalities and behaviours. And there is a whole different order of analysis to be done at the societal level with regard to toilet hygiene, capitalism, economic development, and symbolic pollution (Cluley & Dunne, ; Herring, ; Nixon & Gabriel, ; Shankar, Whittaker, & Fitchett, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ojha and Pramanick (1992) showed that Hindu mothers started personalities and behaviours. And there is a whole different order of analysis to be done at the societal level with regard to toilet hygiene, capitalism, economic development, and symbolic pollution (Cluley & Dunne, 2012;Herring, 2014;Nixon & Gabriel, 2015;Shankar, Whittaker, & Fitchett, 2006).…”
Section: Limitations and Future Researchmentioning
confidence: 99%